Genetic Deletion of miR-430 Disrupts Maternal-Zygotic Transition and Embryonic Body Plan - Liu, Yun; Zhu, Zeyao; Ho, Idy H. T.; Shi, Yujian; Li, Jianzhen; Wang, Xia; Chan, Matthew T. V.; Cheng, Christopher H. K. (Frontiers in Genetics, 2020)
MiR-430 is considered an important regulator during embryonic development, but genetic loss-of-function study is still lacking. Here we demonstrated that genetic deletion of the miR-430 cluster resulted in developmental defects in cell movement, germ layer specification, axis patterning and organ progenitor formation in zebrafish. Transcriptome analysis indicated that the maternally provided transcripts were not properly degraded whereas the zygotic genome expressed genes were not fully activated in the miR-430 mutants. We further found that a reciprocal regulatory loop exists between miR-430 and maternally provided transcripts: the maternally provided transcripts (Nanog, Dicer1, Dgcr8, and AGOs) are required for miR-430 biogenesis and function, whereas miR-430 is required for the clearance of these maternally provided transcripts. These data provide the first genetic evidence that miR-430 is required for maternal-zygotic transition and subsequent establishment of embryonic body plan.